2018
DOI: 10.1111/jvh.12964
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen positivity during pregnancy and risk of gestational diabetes mellitus: A systematic review and meta‐analysis

Abstract: Chronic hepatitis B virus (HBV) infection is a prevalent public health issue worldwide. Its impact on important pregnancy outcomes, such as gestational diabetes mellitus (GDM), has not been clearly established. The findings from published studies are inconsistent. In this systematic review and meta-analysis, we aimed to clarify whether HBV infection manifested during pregnancy is associated with an increased risk of GDM. We searched MEDLINE and EMBASE for cohort studies and case-control studies that investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 60 publications
(257 reference statements)
5
33
0
1
Order By: Relevance
“…A subsequent meta-analysis published in 2018 reported similar findings. 19 Our study, which includes large numbers of women born across all regions of the world also shows an association between HBV and GDM, but, consistent with the systematic review, not in women from North-East Asia where the prevalence of both HBV and GDM is high.…”
Section: Main Findingssupporting
confidence: 88%
“…A subsequent meta-analysis published in 2018 reported similar findings. 19 Our study, which includes large numbers of women born across all regions of the world also shows an association between HBV and GDM, but, consistent with the systematic review, not in women from North-East Asia where the prevalence of both HBV and GDM is high.…”
Section: Main Findingssupporting
confidence: 88%
“…The results of previous studies on the association between the HBsAg carrier status and subsequent risk of HDP, GDM and preterm birth were conflicting. Although several previous studies suggested that HBsAg carrier status is associated with the risk of HDP, GDM and preterm birth, other studies did not . This inconsistency may also be explained by differences in race, HBV endemic areas, diagnostic criteria and the confounding variables included in their analyses.…”
Section: Discussionmentioning
confidence: 86%
“…By reviewing the possible causal mechanisms reported from previously published studies, we constructed a DAG framework for the effects of maternal HBsAg carrier status on the occurrence of selected APOs (Figure ). The prepregnancy BMI is substituted by maternal weight before pregnancy and height, as this parameter does not normally exist .…”
Section: Methodsmentioning
confidence: 99%
“…These observations would be compatible with the notion that chronic HBV infection has co-evolved with humans without jeopardizing pregnancy outcome so as to ensure transmission to successive generations. On the other hand, there are also studies which found associations with preterm birth (PTB) [10,13,[16][17][18][19][20][21], pregnancy hypertensive disorders (PHD) [13,15], gestational diabetes mellitus (GDM) [22][23][24][25], low-birthweight (LBW) infants [17,26,27], asphyxia [28], and intrauterine fetal death (IUFD) and stillbirth (SB) [13,17]. The reason(s) for the con icting and contradicting observations remains unclear, but as these reports were based on different racial/ethnic groups in different locations, one possible factor could have been racial/ethnic differences among the different studies.…”
Section: Introductionmentioning
confidence: 99%